Juana Manuela Gorriti and Cora Olivia: The Issue of Slavery and The Promotion of The Book Panoramas de la vida in La Ondina del Plata - Buret, María Florencia (Meridional. Revista Chilena de Estudios Latinoamericanos, 2016)
This paper is structured around two separate analyses: Juana Manuela Gorriti’s authorial figure and her narrative’s approach to the issue of slavery. First we study the narrative treatment of slavery in three stories –“La quena”, “El ángel caído” and “Peregrinaciones de una alma triste”– emphasizing her commitment to this issue. Secondly, we analyze how Cora Olivia promotes Gorriti’s novelistic production, highlighting her sensibility in view of the unjust and rootlessness situations lived by slaves. A detailed reading of her article –“Conversaciones literarias”, published in La Ondina del Plata in 1877– allows us to see that next to the explicit objective of supporting the novelistic genre by mentioning “good novels” such as “La quena”, there is another implicit goal: to refute and correct the first critical judgments emitted against Gorriti’s writing. The detection of this covert defense, plus the identification of other data from the text and its context, allows us to formulate a hypothesis about the identity of Cora Olivia.